Larvicides Activity of Krokot Extract into Aedes aegypti Mortality - Fanani, Zaenal; Hidayah, Noor; Yulianti, Nur Fajria (Jurnal Sains dan Kesehatan, 2024)
Dengue Hemorrhagic Fever (DHF) is transmitted by Aedes aegypti, one of controlling vectors which is larvicides. Synthetic larvicides cause several problems so that alternative natural larvicides are used. One of which is the krokot (Portulaca oleracea, L.), the content such as flavonoids, tannins, alkaloids, and saponins can be used as larvicides. This study aims to determine the larvicides activity of krokot extract on mortality of Aedes aegypti. The study was conducted using experimental quantitative research. The study was conducted by pouring the ethanol extract on 25 larvae and repeated 3 times, for 24 hours. The result of larvae mortality test at concentrations of 4%, 5% and 6%, namely 39%, 57% dan 72%. LC50 value from krokot extract on the larvae mortality, that is equal to 9.294%. Based on the study, it can be concluded that the krokot ethanol extract is able to kill 50% of the Aedes aegypti larvae population.   Keywords:          krokot, ethanol extract, Aedes aegypti, mortality